Case report of asymptomatic situs inversus totalis with dextrocardia in primigravida: Is cesarean section necessary? - Arifia, Erina; Putra, Gagah Buana; Wahyuni, Alfaina; Rahmiati, Nurmaita (Institute of Computer Science (IOCS), 2025)
Introduction: Situs inversus, a congenital anomaly, is defined by the transportation of thoracic and abdominal organs. A variety during pregnancy this condition has often a challenge for obstetricians, gynecologists, and midwives as there is concern about cardiovascular dysfunction, leading to recommendations for cesarean section. Case Report: A 28-year-old primigravida at 40 gestational weeks. She was admitted arrival at the emergency room. Dextrocardia was already present, as was sinus inversus totalis and antenatal assessment relevealed no abnormalities. Patient underwent a spontanous vaginal delivery of a healthy male infant with normal birth weight. Discussion: Situs inversus totalis with dextrocardia does not compromise organ function or the typical physiological changes of pregnancy including cardiovascular system. Therefore, routine cesarean section is not indicated for these patients unless other obstetric factor necessitate it, as this condition does not independently contribute to increased maternal or fetal complications. Conclusion: Delivery of a pregnancy, dextrocardia, and situs inversus totalis via vaginal delivery is feasible without any significant cardiovascular risks. Cesarean section was not necessary unless other obstetric indications.